Eclipsing the innermost accretion disc regions in AGN. Issue 4 (May 2016) - Sanfrutos, M; Miniutti, G.; Dovčiak, M.; Agís–González, B.
Abstract: Variable X‐ray absorption has been observed in active galactic nuclei (AGN) on several time scales. Observations allow us to identify the absorber with clouds associated either with the clumpy torus (parsec scales, long timescales) or with the broad line region (BLR) (short timescales). In the latter, the cloud size has been estimated to be of the order of few gravitational radii from the observed absorption variability. Such small cloud sizes are comparable to the X‐ray emitting regions so that a detailed modeling of occultation events in AGN has the potential of enabling us to infer accurately the geometry of the system. We have developed a relativistic X‐ray spectral model for occultation events and we present here theoretical predictions on the different observables that can be inferred by studying X‐ray eclipses in simulated XMM Newton data. These include the size of the X‐ray emitting regions as well as more fundamental parameters such as the black hole spin and the system inclination. We find that absorption varies as a function of the energy range and that its maximum takes place when the approaching part of the accretion disc is covered. Therefore we study the hard‐to‐soft (H/ S) ratio light curves produced during an eclipse and use them to characterise the properties of the inner accretion disc in a new model‐independent way. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)